Conservative Treatment of Tuberculosis of the Spine in Patients with no Neurological Deficits - Flamerz, Bassam M.; Faraj, Moneer K.; Ibrahim, Ahmed H. (AL-Kindy College Medical Journal, 2019)
Background: Patients who have both neurological impairment and kyphotic deformity can be treated medically, and this treatment can be achieved with anti-tuberculous drugs alone. Objective: To evaluate conservative medical management of patients with tuberculosis of the spine (Pott disease). The prognostic significance of various clinical, radiological, and long-term follow-up findings in these patients was also evaluated. Methods: Between January 2009 and January 2018 data were collected prospectively at The Neurosciences Hospital/ Baghdad/ Iraq in 44 patients with Pott disease in the thoracic and lumbar spine. These patients had no major neurological deficits or severe spinal deformities. The study population consisted of 21 male (48%) and 23 female (52%) patients, with a mean age of 42.1 years (range 10–70 years). The most common region of Pott disease was the thoracolumbar junction (18 cases; 41%), followed by the thoracic (16 cases; 36%) and lumbar (10 cases; 23%) regions. With the exception of two cases, all had kyphotic angles less than 30°. At presentation, 20 patients had neurological signs of spinal cord compression during clinical examination. Clinical , radiological, and laboratory investigations findings were used in all cases for diagnosis. All patients were treated with anti-tuberculous drugs, and the disease in only two (4.5%) was resistant to the regimen. The follow up period was 24 months. Forty-two (95.4%) of the 44 patients were successfully treated with conservative medical management and attained acceptable spinal deformity angles, and none of these patients had any residual instability, radiculopathy, or neurological compromise. Only 4.5% of the patients experienced residual spine deformity (as much as a 30° kyphotic angle), which was clinically obvious but biomechanically stable. Conclusions: Patients with Pott disease in the lumbar and thoracic regions, without neurological deficits or kyphosis, can be treated conservatively in the vast majority of cases. Indications for surgery need to be redefined given these new data.